2022
DOI: 10.1093/infdis/jiac250
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Breakthrough Infection After Heterologous Prime-Boost Vaccination Induces a Vigorous Antibody Response

Abstract: Infection by the SARS-CoV-2 variant Omicron is usually asymptomatic or mild and appears to be poorly immunogenic at least in unvaccinated individuals. Here, we found that healthcare workers vaccinated with two doses of Sputnik V and a booster dose of ChAdOx1 mount a vigorous neutralizing-antibody response after Omicron breakthrough infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, since in the Austrian population the number of breakthrough infections despite immunization is rising [49], we can assume that a significant proportion of vaccinated participants also received an infection-induced booster. Overall evidence suggests that individuals with hybrid immunity may possess a more robust immune responses [30,[50][51][52][53][54] and a higher protection from infection and severe COVID-19 [55,56] compared to individuals with either vaccination or previous infection alone. It is hypothesized that the protective advantage in individuals with hybrid immunity is that they generate more SARS-CoV-2 receptor binding domain-specific memory B cells and variant-neutralizing antibodies and a distinct population of interferon gamma and Interleukin 10-expressing memory SARS-CoV-2 spike-specific CD4+ T cells than previously naive individuals [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, since in the Austrian population the number of breakthrough infections despite immunization is rising [49], we can assume that a significant proportion of vaccinated participants also received an infection-induced booster. Overall evidence suggests that individuals with hybrid immunity may possess a more robust immune responses [30,[50][51][52][53][54] and a higher protection from infection and severe COVID-19 [55,56] compared to individuals with either vaccination or previous infection alone. It is hypothesized that the protective advantage in individuals with hybrid immunity is that they generate more SARS-CoV-2 receptor binding domain-specific memory B cells and variant-neutralizing antibodies and a distinct population of interferon gamma and Interleukin 10-expressing memory SARS-CoV-2 spike-specific CD4+ T cells than previously naive individuals [57].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a waning of immunity against SARS-CoV-2 virus after a primary two-dose series, regardless of platform. 37 The waning of effects can be linked to decreased concentrations in serum antibody levels, a lower initial response, underlying health conditions, or a combination of any of the aforementioned. Additionally, as SARS-CoV-2 has adapted to its new human host, mutations exhibiting selective sweeps have been observed, with many of these mutations showing various degrees of antibody-recognition escape.…”
Section: Discussionmentioning
confidence: 99%
“…However, since in the Austrian population the number of breakthrough infections despite immunization is rising [47], we can assume that a significant proportion of vaccinated participants also received an infection-induced booster. Overall evidence suggests that individuals with hybrid immunity may possess a more robust immune responses [29,[48][49][50][51][52] and a higher protection from infection and severe COVID-19 [53,54] compared to individuals with either vaccination or previous infection alone. It is hypothesized that the protective advantage in individuals with hybrid immunity is that they generate more SARS-CoV-2 receptor binding domain specific memory B cells and variant-neutralizing antibodies and a distinct population of interferon gamma and Interleukin 10-expressing memory SARS-CoV-2 spike-specific CD4+ T cells than previously naive individuals [55].…”
Section: Discussionmentioning
confidence: 99%